Analysis of Intercultural Communication in Implementation of Independent Student Exchange Program - Eka Yusup; Ilham Gemiharto (Yayasan Ilomata, 2022)
Since 2021 the Ministry of Education, Culture, Research and Technology has launched the Independent Student Exchange program as part of the Merdeka Campus Program. The Independent Student Exchange Program began to open online registration in June 2021, and has now entered the program implementation stage. One of the main goals of the Independent Student Exchange Program is to explore and get to know the cultural diversity of the archipelago and make friends with fellow students from different cultural backgrounds. This study aims to analyze aspects of intercultural communication that occur in the implementation of the Independent Student Exchange Program, such as how cultural interactions among students, how each student displays their cultural identity, and how to adapt to fellow students. This research uses a qualitative approach, an exploratory paradigm, in a case study perspective. The data collection process was carried out under natural conditions in the form of observation, in-depth interviews and documentation studies. This study concludes that although there are many differences in cultural backgrounds, students try to adapt to their peers who have different cultural backgrounds. The main obstacle in intercultural communication is the language barrier, because even though both speak Indonesian, the influence of local languages is still very strong, so sometimes the same vocabulary has different meanings and meanings. The results of the study also found several cases related to stereotypes against certain ethnic groups, the existence of ethnocentrism among program participants and various difficulties in adapting to fellow program participants.